A high-performance silicon photoanode enabled by oxygen vacancy modulation on NiOOH electrocatalyst for water oxidation. Issue 14 (30th March 2020) - Cai, Qian; Hong, Wenting; Jian, Chuanyong; Liu, Wei
Abstract : NiFe nanoparticles which are deposited onto the n-Si/Ni/NiOOH photoanode surface lead to high OER performance by acting as a co-catalyst and creating oxygen vacancies. Abstract : Silicon (Si) is an attractive photoanode material for photoelectrochemical (PEC) water splitting. However, Si photoanode towards the oxygen evolution reaction (OER) is highly challenged due to its poor stability and catalytic inactivity. The integration of highly active electrocatalysts with Si photoanodes has been considered to be an effective strategy to improve their OER performance by accelerating the reaction kinetics and inhibiting Si photocorrosion. In this work, ultra-small NiFe nanoparticles are deposited onto the n-Si/Ni/NiOOH surface to improve the activity and stability of Si photoanodes by engineering the electrocatalyst and Si interface. Ultra-small NiFe nanoparticles can introduce oxygen vacancies via modulating the local electronic structure of Ni hosts in NiOOH electrocatalysts for fast charge separation and transfer. Besides, NiFe nanoparticles can also serve as a co-catalyst exposing more active sites and as a protection layer preventing Si photocorrosion. The as-prepared n-Si/Ni/NiOOH/NiFe photoanode exhibits excellent OER activity with an onset potential of 1.0 V versus reversible hydrogen electrode (RHE) and a photocurrent density of ∼25.2 mA cm −2 at 1.23 V versus RHE. This work provides a promising approach to design high-performance Si photoanodes by surface electrocatalyst engineering.